Measurement of Mitochondrial dNTP Pools - Martí, Ramon (Methods Mol Biol, 2012)
Because deoxyribonucleoside triphosphates (dNTPs) are the critical substrates for DNA replication and repair, dNTP pools have been studied in context of multiple basic biochemical processes. Over the last 12 years, interest in dNTPs, and specifically the mitochondrial dNTP pools, has expanded to biomedical science because several mitochondrial diseases have been found to be caused by dysfunctions of several enzymes involved in dNTP catabolism or anabolism. Techniques to reliably measure mitochondrial dNTPs should be sensitive and specific to avoid interference caused by the abundant ribonucleotides. Here, we describe detailed protocols to measure mitochondrial dNTPs from two specific samples, cultured skin fibroblasts and mouse liver. The methods can be easily adapted to other types of samples. The protocol follows a polymerase-based method, which is the most widely used approach to measure dNTP pools. Our description is based on the latest update of the technique, which minimizes the potential interference from ribonucleotides.